2004
DOI: 10.1212/01.wnl.0000134605.61307.de
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss as the first feature of late-onset axonal CMT disease due to a novel P0 mutation

Abstract: A Czech family with three individuals carrying a novel mutation, 290 A-->T (Glu97Val), in the myelin protein zero gene (P0) is reported. The two eldest carriers developed progressive sensorineural hearing loss and abnormal pupillary reaction at age 18. These preceded the onset of the classic signs of Charcot-Marie-Tooth disease (CMT) by more than a decade. Sural nerve biopsy and nerve conduction studies were compatible with the axonal type of CMT. The authors show that progressive hearing loss can be the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…The manifestation of progressive sensorineural hearing loss and abnormal pupillary reaction may indicate that the mutation in MPZ results in an abnormality of cranial nerves in combination with and abnormality in other peripheral nerves (Seeman et al, 2004). Starr et al (2003) found that both the sural and …”
Section: Discussionmentioning
confidence: 99%
“…The manifestation of progressive sensorineural hearing loss and abnormal pupillary reaction may indicate that the mutation in MPZ results in an abnormality of cranial nerves in combination with and abnormality in other peripheral nerves (Seeman et al, 2004). Starr et al (2003) found that both the sural and …”
Section: Discussionmentioning
confidence: 99%
“…EM revealed normal myelin packing and periodicity whereas occasional myelin sheaths were abnormally thick because of redundant loop formation. Another patient [69] showed profound loss of large myelinated fibers, multiple clusters of regenerated axonal sprouts, and no onion bulb formations.…”
Section: Histopathologymentioning
confidence: 99%
“…Present OAEs are sometimes associated with nonrecordable or highly altered ABRs. Progressive deafness in a MPZ mutation carrier family was the first sign of CMT disease, preceding signs of peripheral neuropathy 1 10 years [Seeman et al, 2004].…”
Section: A Genetically Heterogeneous Example (Dominant Recessive and mentioning
confidence: 99%